2014
DOI: 10.1245/s10434-014-4174-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Animal Model for Locally Advanced Breast Cancer

Abstract: Background Locally advanced breast cancer (LABC) poses complex management issues due to failure of response to chemotherapy and progression to local complications such as skin erosion, superinfection and lymphedema. Most cell line and animal models are not adequate to study LABC. Methods A patient-derived xenograft (IOWA-1T) from a patient with LABC was characterized for expression profile, short tandem repeat (STR) profile, oncogenic mutations, xenograft growth and response to therapy. Results STR profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Previous tumorigenesis studies demonstrated a significant effect of SUMO inhibitors to repress the outgrowth of basal breast cancer xenografts (Bogachek et al., 2014, Bogachek et al., 2015b). However, we noticed that after 1 month approximately 40% of the mice treated with anacardic acid developed small xenografts and we hypothesized that this was possibly due to outgrowth of non-CSC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous tumorigenesis studies demonstrated a significant effect of SUMO inhibitors to repress the outgrowth of basal breast cancer xenografts (Bogachek et al., 2014, Bogachek et al., 2015b). However, we noticed that after 1 month approximately 40% of the mice treated with anacardic acid developed small xenografts and we hypothesized that this was possibly due to outgrowth of non-CSC.…”
Section: Resultsmentioning
confidence: 99%
“…IOWA-1T was derived as described by Bogachek et al., 2015a, Bogachek et al., 2015b and is available through the ATCC. MDA-MB-436 and HCT116 were obtained from the ATCC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data, taken together with the well-established safety profile of clofazimine, prompted us to confirm its activity using in vivo models. We chose BT-20 as a somatic cancer cell line with a proven track of Wnt-dependent growth [24,59], and the IOWA-1T line corresponding to the chemoresistant cancer progenitor population [29], which has also been described to have and depend on high levels of Wnt signaling [60,61]. The second line was also our obvious choice for combination treatment, since it is particularly relevant for chemoresisitant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Basal/HER2+ breast cancer shows poorer survival than other phenotypes [ 29 , 30 ]. We examined the expression of HER2, along with luminal (PR, ER-α, keratin 18, FOXA1/HNF3α, and AGR2) [ 31 ], basal (EGFR, SPARC, Vimentin, and caveolin1–2), pluripotent (CD44 [ 32 ], and Stat3α/β, OCT-4, SOX2, and Nanog [ 33 , 34 ]) and prognosis (CD146 and VDR) markers by western blotting. CD146 [ 35 ], and VDR [ 36 , 37 ] are associated with poor and excellent prognosis, respectively.…”
Section: Discussionmentioning
confidence: 99%